Rethinking the city reconfiguration and fragmentation - Molder, Maria Filomena 1950-; Conceição, Nélio; Fonseca, Nuno (Routledge, Taylor & Francis Group, 2025)
"An exploration of the complex relationship between aesthetics, the arts and the city, Rethinking the City: Reconfiguration and Fragmentation will appeal to scholars across various disciplines, including philosophy, urban sociology and geography, anthropology, political theory and visual and media studies"--
Keywords: Stadtbild; Stadtsoziologie; Stadt; Cities and towns; Sociology, Urban; Art and cities; Villes; Sociologie urbaine; cities; urban sociology; Aufsatzsammlung